Alteration in the in vitro activity of milk leukocytes during different parity in high yielding cross-bred cows. Issue 4 (3rd July 2016) - Sharma, Tripti; Kumar Das, Pradip; Ghosh, Probal Ranjan; Banerjee, Dipak; Chandra Das, Bikash; Mukherjee, Joydip
Abstract: In vitro activity of milk leukocytes (viz. neutrophils, lymphocytes and macrophages) was evaluated in forty-eight (48) clinically healthy high-yielding cross-bred cows of mid-lactation stage (100–200 days of lactation), divided into four groups namely 1st parity ( n  = 12), 2nd parity ( n  = 12), 3rd parity ( n  = 12) and 4th and above parity ( n  = 12). Milk samples were taken (250 ml/cow) were taken. Milk somatic cell counts (SCC) and differential leukocyte counts (DLC) were performed microscopically. In vitro phagocytic index (PI) of milk neutrophils and macrophages was evaluated by colorimetric nitro blue tetrazolium reductive assay. Mitogen-induced milk lymphocyte blastogenic response was measured by colorimetric MTT (tetrazolium) assay after isolation of the milk leukocytes by density gradient centrifugation. Milk SCC differed significantly ( p  < 0.01) between different parity. Cows of 4 and above parity showed significantly ( p  < 0.01) higher milk SCC compared to primiparous cows. There was no significant difference in milk DLC during different parities in high-yielding cross-bred cows. There was a significant ( p  < 0.01) variation in lymphocyte blastogenesis amongst parity. The highest value of lymphocyte blastogenesis was seen at 3rd parity, whereas lowest value was obtained in the cows of both 1st and 4th or above parity. PI of milk neutrophils did not differ significantly between parity. PI of milk macrophages was significantly ( p  < 0.01) higher in 3rd parity and lower ( p  < 0.01) in 1st and 4th parities. The study indicated that depressed activity of milk lymphocytes and macropages was lower and SCC was higher in the cows of 4th and above parity indicating more mammary stress and hence susceptible to udder infection and mastitis. Therefore, better care and managemental interventions should be taken around these periods.